2010
DOI: 10.1007/s10562-010-0403-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on Solvent/Alkoxide Molar Ratios on Synthesis Zirconia Nanoparticles for Tungstated Zirconia Catalysts Over Esterification

Abstract: A series of nanocrystal zirconia samples were synthesized, characterized and studied for the esterification reaction. The results showed that the solvothermal method under different solvent/alkoxide molar ratios led to remarkable effect on the amount of carbon residue remained on the surface of catalysts resulting in the difference in proton species-support interaction behavior. Moreover, the esterification activity of W/ZrO 2 varied distinctly with the solvothermal synthesis condition of nanocrystal zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It reveals that strontia loading decreases the BET surface area sharply, which is in good agreement with studies conducted by other researchers. 20 It was concluded that strontia crystals assemble on surface or in pores of sulfated zirconia. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It reveals that strontia loading decreases the BET surface area sharply, which is in good agreement with studies conducted by other researchers. 20 It was concluded that strontia crystals assemble on surface or in pores of sulfated zirconia. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Due to high acid strength and good stability in comparison with sulfated zirconia, the WO x /ZrO 2 composites also enable wide applications in diverse acid-catalytic reactions. [19][20][21][22][23][24][25][26] Notably, the catalytic activity was demonstrated to be dependent on surface acid density, which was closely associated with the density (W atoms/nm 2 ) and dispersion (electronic structure and domain size) of WO x species supported on ZrO 2 . Therefore, the surface acid density of WO x /ZrO 2 can be controlled by tuning tungsten amount, calcination temperature, and surface area of ZrO 2 supports.…”
Section: Introductionmentioning
confidence: 97%
“…Through incorporating tungsten on zirconia, the WO x /ZrO 2 composites were first reported as novel solid superacid catalysts for isomerization of butane and pentane [18] . Due to high acid strength and good stability in comparison with sulfated zirconia, the WO x /ZrO 2 composites also enable wide applications in diverse acid‐catalytic reactions [19–26] . Notably, the catalytic activity was demonstrated to be dependent on surface acid density, which was closely associated with the density (W atoms/nm 2 ) and dispersion (electronic structure and domain size) of WO x species supported on ZrO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different alcohols were indeed investigated by Anandan et al [24], but the obtained samples were all monoclinic. The aim of the present work is thus to determinate if the solvent is a valid synthesis parameter with the same importance as temperature or the nature of the metal precursor or its concentration [25].…”
Section: Introductionmentioning
confidence: 99%